measurement and disclosure of visual production in the Iraqi media network according to international accounting standards - Rae'ed hazim jodah / Khawla Hussein Hamdan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The requirements of accounting measurement and disclosure for the visual production industry in Iraq differ from accounting standards, as accounting recognition according to local accounting rules requires conditions and events that differ from those required by international standards, and that the adoption of international accounting standards leads to the possibility of comparison between the financial statements of companies and what serves many parties, including investors In making their investment decisions, the research aims to identify what is visual production in companies in accounting thought and to identify shortcomings in measurement and disclosure of treatments in visual production companies under the local accounting rules and the unified accounting system by comparing it with the relevant international accounting standards